Are Emerging Markets Efficient? The Impact of Dividend Payment on The Company Financial Performance: Evidence from The Polish Stock Market - Andrzej ZYGULA (Communications of International Proceedings, 2022)
The aim of the article is to present the results of the research on the impact of the dividend policy on the economic efficiency of companies. The study was conducted on public companies that were listed on the Polish stock market in 1998-2019. The data necessary for the research was obtained from the Notoria Serwis database. The study was conducted using the panel models. The research results showed that the impact of the decision to pay dividends on the financial results of companies (ROA, ROE) was statistically significant and positive. In addition, it was also demonstrated that the dividend payout rate (DPR) did not affect the financial results of companies. The obtained results are consistent with the results of some global studies, that provide ambiguous results on the impact of the dividend policy on the economic efficiency of companies. Therefore, the answer to the question whether dividend payments carry information about the financial situation of a given entity remains an open issue.
Keywords: Dividend Policy; Dividends; Corporate Earnings; Economic Efficiency